Rapid clinical diagnostic variant investigation of genomic patient sequencing data with iobio web tools. Issue 6 (23rd April 2018) - Ward, Alistair; Karren, Mary A.; Di Sera, Tonya; Miller, Chase; Velinder, Matt; Qiao, Yi; Filloux, Francis M.; Ostrander, Betsy; Butterfield, Russell; Bonkowsky, Joshua L.; Dere, Willard; Marth, Gabor T.
Abstract : Introduction: Computational analysis of genome or exome sequences may improve inherited disease diagnosis, but is costly and time-consuming. Methods: We describe the use of iobio, a web-based tool suite for intuitive, real-time genome diagnostic analyses. Results: We used iobio to identify the disease-causing variant in a patient with early infantile epileptic encephalopathy with prior nondiagnostic genetic testing. Conclusions: Iobio tools can be used by clinicians to rapidly identify disease-causing variants from genomic patient sequencing data.